2023
DOI: 10.1002/anie.202217724
|View full text |Cite
|
Sign up to set email alerts
|

Highly Enantioselective Construction of Multifunctional Silicon‐Stereogenic Silacycles by Asymmetric Enamine Catalysis

Abstract: We report the first highly enantioselective construction of silicon‐stereocenters by asymmetric enamine catalysis. An unprecedented desymmetric intramolecular aldolization of prochiral siladials was thus developed for the facile access of multifunctional silicon‐stereogenic silacycles in high to excellent enantioselectivity. With an enal moiety, these adducts could be readily elaborated for the diverse synthesis of silicon‐stereogenic compounds, and for late‐stage modification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(2 citation statements)
references
References 138 publications
0
2
0
Order By: Relevance
“…1,2 The broad spectrum of biological activity exhibited by indole derivatives renders their synthesis a subject of considerable interest in chemistry and medicine. [3][4][5][6][7][8] The promising applications of cascade reactions to access a variety of natural product scaffolds make them one of the leading and fascinating strategies towards development in organic synthesis. [9][10][11][12] Encouraged by the advancement of cascade reactions, we targeted pyrrolo [1,2-a]indoles possessing a unique 6-5-5 tricyclic ring skeleton.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 The broad spectrum of biological activity exhibited by indole derivatives renders their synthesis a subject of considerable interest in chemistry and medicine. [3][4][5][6][7][8] The promising applications of cascade reactions to access a variety of natural product scaffolds make them one of the leading and fascinating strategies towards development in organic synthesis. [9][10][11][12] Encouraged by the advancement of cascade reactions, we targeted pyrrolo [1,2-a]indoles possessing a unique 6-5-5 tricyclic ring skeleton.…”
Section: Introductionmentioning
confidence: 99%
“…We also demonstrated that the C/Si switch is feasible for the syn thesis of chiral sila-fluorenes. However, remarkably lower enantioselectivity was observed, probably due to a detrimental longer C–Si bond for chiral induction ( 3r – 3s ) …”
mentioning
confidence: 99%